Diagnosis of Synergy Versus SCM Improvement - Olfa Jellouli (International Journal of Supply Chain Management, 2014)
Faced with globalization and competition, leaders are looking for new concepts allowing them to keep the improvement of part of the market. Synergy is a way for his last in the case of multi- sites. It has now become a key factor of competitiveness. The question is then how to diagnose a plan of action in order to achieve excellence in industrial management. This is the subject of the following article. Its a contribution for prcising typology of synergy.